Ultrafast dynamics of protein collapse from single-molecule photon statistics - Nettels, Daniel (National Academy of Sciences, 2007)
We use the statistics of photon emission from single molecules to probe the ultrafast dynamics of an unfolded protein via Förster resonance energy transfer. Global reconfiguration of the chain occurs on a time scale of ≈50 ns and slows down concomitant with chain collapse under folding conditions. These diffusive dynamics provide a missing link between the phenomenological chemical kinetics commonly used in protein folding and a physical description in terms of quantitative free energy surfaces. The experiments demonstrate the potential of single-molecule methods in accessing the biologically important nanosecond time scales even in heterogeneous populations.